(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Effects of 20, 50, 100 and 150 ppm TIBA on growth and yield of BARI soybean -5 were evaluated. Plant height reduced significantly due to 50, 100 and 150 ppm TIBA. There was an increasing tendency in number of leaves per plant with increase in the concentrations of TIBA. Number of leaves and dry weight of shoot significantly increased following TIBA applications. Yield components viz. number of branches per plant, number of pods per plant, fresh weight and dry weight of pods per plant, 100 seed weight and seed yield per plant increased significantly due to 100 and 150 ppm TIBA application, whereas, most of the yield parameters decreased due to 20 ppm TIBA. Yield per plant increased by 7.32, 18.81 and 21.50% following 50, 100 and 150 ppm TIBA. Pigment content of leaf was not affected significantly due to TIBA application. Amongst all the concentrations 150 ppm TIBA produced best stimulation. J. Asiat. Soc. Bangladesh, Sci. 40(1): 89-96, June 2014